2012
DOI: 10.1016/s1995-7645(12)60187-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality among HIV–infected patients initiating anti retroviral therapy at a tertiary care hospital in Eastern India

Abstract: Risk of mortality is increased when ART is initiated at advanced stages of immunosuppression denoted by low serum albumin levels and CD4 cell counts. This highlights the importance of early detection of HIV infection, early management of opportunistic infections including tuberculosis and timely initiation of the antiretroviral drugs in the resource-limited countries, now available free in the Indian national ART programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
4
20
2
Order By: Relevance
“…Serum albumin has also been inversely associated with IL-6 levels, a proinflammatory cytokine, which has been shown to upregulate HIV replication (Ward et al 1999). Adult ART-naive patients with low baseline serum albumin had an eight times increased risk of death than those with higher serum albumin levels, and patients with CD4 count of less than 100 cells were two times at higher risk of death compared to those with higher CD4 counts (Bhowmik et al 2012). Mild anemia was found to be common in ARV-naïve Thai and Cambodian children without advanced HIV.…”
Section: Discussionmentioning
confidence: 90%
“…Serum albumin has also been inversely associated with IL-6 levels, a proinflammatory cytokine, which has been shown to upregulate HIV replication (Ward et al 1999). Adult ART-naive patients with low baseline serum albumin had an eight times increased risk of death than those with higher serum albumin levels, and patients with CD4 count of less than 100 cells were two times at higher risk of death compared to those with higher CD4 counts (Bhowmik et al 2012). Mild anemia was found to be common in ARV-naïve Thai and Cambodian children without advanced HIV.…”
Section: Discussionmentioning
confidence: 90%
“…Hypoalbuminemia, present in diverse chronic inflammatory states and a known risk factor for HIV disease progression and mortality as well as post-ART TB in resource-limited settings, had the strongest independent association with TB risk in our multinational population. [3,42] Until now, however, only very limited data have been available for CRP, IP-10, or LPS. One previous study (at a single center in Uganda) found that adults with pre-ART CRP >5 mg/L were at increased risk of ART-associated TB within of the first year of treatment, but only eight TB cases were identified during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tuberculosis was found to be the most important cause of death and it caused 48% of the total death and other studies also showed greater estimate than this current findings [15,[18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 41%
“…When ART is initiated at advanced stage of immune suppression denoted by low serum albumin level and CD4 cell count, risk of mortality is increased. This highlights the importance of timely initiation of ART drugs, namely, early detection of HIV infection and early managements of opportunistic infection including tuberculosis in the resource limited countries [15]. Similarly, the current study aimed to supplement the available evidences of mortality of patients on ART program in Ethiopia.…”
Section: Introductionmentioning
confidence: 97%